Liver cell-mediated mutagenesis of mammalian cells by liver carcinogens. - Langenbach, R (1978)
A cell-mediated mutagenesis assay using primary cultures of rat liver cells and V79 Chinese hamster cells has been developed. Liver carcinogens and their structural analogues were studied. Mutations in the V79 cells were characterized by resistance to ouabain. Cocultivation of the liver cells and V79 cells in the presence of the carcinogens N-nitrosodimethylamine, N-nitrosodiethylamine, and aflatoxin B1 caused the induction of ouabain-resistant mutants of V79 cells. In the absence of liver cells, the carcinogens did not induce ouabain resistance. The analogues N-nitrosomethyl-tert-butylamine and aflatoxin G2 were not mutagenic. The carcinogens exhibited a dose-dependent enhancement of mutation frequency. The mutation frequency also increased with increasing numbers of liver cells seeded. It is suggested that such an experimental system may be useful for screening for chemical carcinogens.